MODELLING MICRO ENTERPRISES’ BEHAVIORAL INTENTION TO ADOPT INTEGRATED ISLAMIC CROWDFUNDING-MICRO ENTERPRISE (IICME) MODEL AS A SOURCE OF FINANCING IN EAST JAVA, INDONESIA - Mohamed Asmy Bin Mohd Thas Thaker; Hassanudin Bin Mohd Thas Thaker (East Java Economic Journal, 2019)
The present study has proposed Integrated Islamic Crowdfunding-Micro Enterprise (IICME) model to assist micro enterprises in meeting their need to access external financial services in East Java, Indonesia. Upon the proposed model, this study examines the behavioural intention of micro enterprises to use IICME model. The primary data are collected from the survey administered to micro enterprises in the East Java (Pasuruan, Malang, Kediri, Ponorogo, and Gresik) and the analysis is conducted using Partial Least Squares (SmartPLS). Furthermore, the model has been validated its acceptance in the field by adopting the extended Technology Acceptance Model (TAM). This study has revealed that the perceived usefulness, perceived easy to use and perceived benefit are found to have a positive impact on the intention of micro enterprises to use IICME model, which later assist them to access to financial services in Indonesia. Furthermore, perceived easy to use has a positive relationship and direct effect with perceived usefulness of micro enterprises to use the IICME model. The findings of this study can be used to develop a specific framework in which to examine other components of using the IICME model’s behavior and to plan appropriate intervention strategies to increase financial accessibility by micro enterprises. JEL: G23; M10